Ethnomedicinal plants used by the tribals of Sudi Konda Forest, East Godavari District, Andhra Pradesh to cure women problems - Aniel kumar, O; Krishna Rao, M; Raghava Rao, T V (Journal of Phytology, 2012)
The paper deals with 27 plant species belonging to 25 genera of 20 families to cure women problems prevalent among the tribals of Sudi konda forest area of East Godavari district, Andhra Pradesh are reported along with local name, methods of administration and prescribed doses.